Is there a link between income inequality and economic growth in the Balkans? - Testing the Kuznets hypothesis - Velkovska, Ivana; Trenovski, Borce; Kozheski, Kristijan (Pravni fakultet - Studijski centar socijalnog rada, Sveučilište u Zagrebu., 2021)
This paper makes an effort to test the Kuznets hypothesis in selected Balkan countries by applying panel data regression analysis for the period 2001-2012. We analyzed the following Balkan countries: 1) EU member states – Croatia, Slovenia, Greece and Bulgaria and 2) EU candidate states – North Macedonia, Bosnia and Herzegovina, Albania and Serbia. The results indicate the existence of the Kuznets curve that is flatter at initial stages of economic development, with income inequality declining at later stages of economic growth. In addition, the EU membership is correlated to lower income inequality, indicating better redistribution efforts in these countries compared to the EU candidate countries.
Keywords: income inequality, Kuznets curve, Gini index, panel data model